Building the spirit of defending the state in the middle of national development - Kunto Wibowo Agung Prodjonoto; Tahan S.L. Toruan (Technium Social Sciences Journal, 2020)
When in the middle of development there are frequent demonstrations accompanied by the destruction of facilities and infrastructure with issues of welfare, this shows the gap between reality and expectations. Security in the midst of efforts to improve welfare is hope, but in fact these demonstrations often occur. For this reason, a human activity system research with the Soft System Methodology method was conducted, (Checkland and Peter Poulter, 2006) in a province in Indonesia with the aim of analyzing the development of awareness and spirit of state defense for national defense and security. Research with the approach of understanding state defense, the concept of the nation, theory (nationalism, awareness and welfare), obtained a detailed conclusion, that it is very important to build awareness of defending the state continuously in the spirit of nationality through early cultivation, formal, non-formal and informal education and socialization , including: (i) An understanding of state defense encourages awareness of state defense, can increase the spirit of public state defense; (ii) Optimizing understanding and awareness of state defense is important to be pursued through early cultivation, formal, non-formal and informal education and socialization, and; (iii) Community involvement in development towards prosperity is also a form of state defense.